The „Soft Power“ Factor in Türkiye’s Georgian Policy - Safarova, Chinara Gabil (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
The Turkish state was one of the first countries to recognize Georgia’s independence in 1991. Since then, political, socio-economic, and cultural cooperation between the two countries has developed. As it is known, since the ninetieth of the 20th century, the Republic of Türkiye has been one of the countries that most actively uses the elements of "soft power" in world politics in general, especially in Caucasian politics. The Republic of Türkiye uses relations in the humanitarian and cultural fields as a "soft power" factor in Georgian politics.